Nicomedes Santa Cruz: la formación de un intelectual público afroperuano - Aguirre, Carlos (Pontificia Universidad Católica del Perú. Fondo Editorial, 2013)
This article reconstructs the trajectory of Nicomedes Santa Cruz, one of the foremost Afro-Peruvian intellectuals of all times, whose presence in the public scene transcended a purely artistic ambit and extended to the terrain of social and political criticism. Nicomedes Santa Cruz was a public intellectual whose multifaceted work addressed the most pressing themes of his time: he was a critic of racism, imperialism and social inequality; he supported the Cuban Revolution; he committed himself to the reforms of the Juan Velasco Alvarado regime; and he promoted international solidarity. Likewise, he tried to combine a commitment to socialism with a defense of Afro-Peruvian culture and rights.

Este artículo reconstruye la trayectoria de Nicomedes Santa Cruz, uno de los más notables intelectuales afroperuanos de todos los tiempos, cuya presencia en la escena pública trascendió el ámbito puramente artístico y se proyectó hacia el terreno de la crítica social y política. Nicomedes Santa Cruz fue un intelectual público que abordó en su multifacético trabajo los temas más candentes de su tiempo: fue un crítico del racismo, el imperialismo y la desigualdad social; apoyó la Revolución Cubana; se comprometió con las reformas del régimen de Juan Velasco Alvarado; y promovió la solidaridad internacional. Asimismo, intentó combinar la apuesta por el socialismo con la reivindicación de la cultura y los derechos de los afrodescendientes.
Keywords: Historia; https://purl.org/pe-repo/ocde/ford#6.01.01